The effects of structural modifications on the electrical and electrochemical properties of stannum based nasicon structured solid electrolytes / Nur Amalina Mustaffa - Nur Amalina , Mustaffa (2017)
In this study, LiSn2P3O12 parent compound was synthesized using water based sol-gel method and the parameters of sol-gel method have been optimized in obtaining minimize impurity of the NASICON compound. Then the effects of structural modifications by partial substitutions using trivalent (Cr3+, Al3+) and tetravalent (Zr4+, Si4+) ions at Sn4+ and P5+ sites on the conductivity and electrochemical properties of the modified NASICON compound were studied. The X-ray diffraction analysis showed that LiSn2P3O12 compound can be indexed to rhomboherdral structure with space group (